The role of the victim's behavior in Causality relation in murder - کیومرث کلانتری; behroz gholizadeh (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2017)
According to art.492 IPC, the crime leads to Qisas or Diya when there is a causal relationship between committed behavior and resulted crime. One of the factors which cuts the chain of causation in the murder is the victim's behavior. The victim can diminish causal relation by "deliberate, consciously or unconsciously" behavior which may be in some cases by omission. However, in some cases, perpetrator's intent is so extensive that the victim's behavior will have no effect on the assignment of crime to him. There are some questions here; what is the victim's behavior effect on the causal relation in murder? What is the effect of perpetrator's intent in the assignment of murder?In this paper, by using descriptive-analytical approach alongside studying the causality relationship between perpetrator behavior and the result of that behavior in murder, the effects of victims behavior on occurrence murder will be studied, and the related questions will be answered by resorting to legal principles and jurisprudence.